Factor Analysis Of Characteristics Of Respondents With Pregnancy Depression At The Bojong Rawalumbu Community Health Center, Bekasi City - Pinem, Lina Herida; Bin Sansuwito, Tukimin; Nambyar, Nisha; Rohmawati (Sahabat Publikasi Kuu, 2023)
Background: Pregnancy is one of the things expected by women in the process of life. However, many women experience difficulties due to physical, social, and psychological changes during pregnancy, there are even some mothers who suffer from psychological disorders such as depression. Perinatal depression occurs in 10-15% of women. One of the causes is a lack of knowledge about the process of pregnancy until the postpartum period which results in birth complications and disrupts the baby's growth and development. Purpose: This study aimed to identify the characteristic factors of respondents associated with prenatal depression. Methods: This research is a quantitative research that uses a cross-sectional design. The sample in this study was 85 respondents of pregnant women using the Edinburgh Postnatal Depression Scale (EPDS) screening tool. Results: The results of this study showed that the factors associated with the incidence of depression in pregnant women were education (p = 0.011), income (P = 0.046), history of domestic violence (p = 0.028), and pregnancy complications (p = 0.043) while the unrelated factors were age (P = 0.098), occupation (P = 0.829) and parity (p = 0.139) with α = 0.05. Conclusion: Education, income, history of domestic violence and history of pregnancy complications affect the incidence of depression in pregnant women. Recommendations: It is expected that the team of health workers, especially midwives and nurses, will not only focus on physical health but mental health also needs attention, and is expected to provide screening services and pregnancy psychology services to identify patients at risk of depression. Keywords: Depression, pregnancy, domestic violence, prenatal.